Talent selection in youth football - Roland Sieghartsleitner; Claudia Zuber; Marc Zibung; Bryan Charbonnet; Achim Conzelmann (Bern Open Publishing, 2019)
Recommended multidimensional models for talent selection are difficult to implement for practitioners in the field. Furthermore, their application has not been established from a scientific point of view, with a lack of clarity concerning how to integrate manifold test results with respect to loading, interaction, and compensation phenomena. Consequently, the question of powerful single predictors for future player status are still of interest within talent research in order to determine promising content for less extensive selection procedures. The aim of the current study is an immediate comparison of the prognostic validity of two frequently used areas within talent selection in youth football: general motor performance (e.g., speed and endurance) and specific motor performance (i.e., technical skills). Participants completed four general and four specific motor performance tests at early adolescence (U13/U14, 133 players) and middle adolescence (U16/U17, 85 players). The area under the curve (AUC) from the receiver operating characteristic was used to compare the prognostic validity of both motor performance areas (predicting U20 player status: professional vs. non-professional). Although no comparison at the four different age levels led to a significant difference (.07 ≤ p ≤ .65), there was a continuous superiority of specific over general motor performance in descriptive AUC values. These descriptive differences reached relevant extent within early adolescence (ΔAUCU13 = .09; ΔAUCU14 =.14) and were partially accounted for by the influence of biological maturation. In line with theoretical considerations and earlier research, these results provide further evidence of the superiority of specific over general motor performance in predicting future player status. Until the applicability of multidimensional models is further established, specific motor performance rather than general performance should be included in less extensive talent selection models, especially in early adolescence.